Analisis Sistem Agribisnis Sub Sektor Hortikultura Di Kabupaten Mukomuko - Usna, Yeni; Mulyasari, Gita; Yuliarso, M Zulkarnain; Sulistyowati, Endang (Jurnal Pertanian Terpadu, 2025)
This study aims to analyze the agribusiness system of the Horticultural Sub-Sector in Mukomuko Regency using the literature review method. This approach examines various aspects of agribusiness, including the supply of production facilities sub-system, cultivation sub-system, product processing sub-system, marketing sub-system, and supporting sub-systems that support the sustainability of the agribusiness system. Mukomuko Regency has good potential for the development of the Horticulture sub-sector by integrating all of these sub-systems in a harmonized and integrated manner.In this study the methodology used was a literature review. This approach involves collecting, reviewing, and analyzing secondary data obtained from various sources, including scientific articles, books, reports, and other publications relevant to the topic of Horticulture subsector agribusiness. The results of this study indicate that the production facilities subsystem, the farming production/cultivation subsystem and the marketing subsystem have been running well and are profitable. While the processing subsystem has not been running well because farmers have not been able to process horticultural products with more modern. Sub-system support has also been running well but not yet optimal